Temporal variations in vertical cloud structure of Jupiter’s Great Red Spot, its surroundings and Oval BA from HST/WFC3 imaging - Anguiano‐Arteaga, A; Pérez‐Hoyos, S; Sánchez‐Lavega, A; Sanz‐Requena, JF; Irwin, PGJ (Wiley, 2023)
In this study, we present the evolution of the properties and vertical distribution of the hazes in Jupiter's Great Red Spot (GRS), its surroundings and Oval BA from 2015 to 2021. To retrieve the main atmospheric parameters, we model the spectral reflectivity of a number of dynamically and/or spectrally interesting regions with a radiative transfer tool that uses an optimal estimator scheme. The spectra of the selected regions are obtained from high-resolution Hubble Space Telescope Wide Field Camera 3 images that cover the spectral range from 200 to 900 nm. The a priori model atmosphere used to describe the various Jovian regions is taken from Anguiano-Arteaga et al. (2021, https://doi.org/10.1029/2021JE006996) for each corresponding area. We find that the biggest variations in the GRS occur in the optical thickness of the stratospheric and tropospheric haze layers starting in 2019 and in the mean size of the tropospheric haze particles in 2018. The absorption spectra of both hazes show little variations among the analyzed regions and years, with the stratospheric haze properties seeming compatible with the chromophore proposed by Carlson et al. (2016, https://doi.org/10.1016/j.icarus.2016.03.008). We report a color change of Oval BA from red to white during these years that, according to our models, can be mostly explained in terms of a decrease in the stratospheric haze optical depth.